2016
DOI: 10.1016/j.jad.2015.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between major depressive disorder and bipolar disorder by auditory steady-state responses

Abstract: We could differentiate between MDD and BD subjects in terms of gamma band ASSR. Our data suggest that the 40-Hz ASSR may be a potential biomarker for differentiation between MDD and BD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 39 publications
3
45
1
Order By: Relevance
“…The 40‐Hz stimulus produces the strongest steady state response, but the exact mechanism is not fully understood . It has been used as an index of the ability for gamma band frequency generation in local cortical networks in mental disorders, including schizophrenia, bipolar disorder, and autism spectrum disorder (ASD) …”
Section: Studies Of Auditory Steady‐state Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The 40‐Hz stimulus produces the strongest steady state response, but the exact mechanism is not fully understood . It has been used as an index of the ability for gamma band frequency generation in local cortical networks in mental disorders, including schizophrenia, bipolar disorder, and autism spectrum disorder (ASD) …”
Section: Studies Of Auditory Steady‐state Responsementioning
confidence: 99%
“…The children were younger than those of previous studies (Table ), and a narrow age range was chosen for this study to avoid the variation with age shown previously. Because ASSR is prominent at rates near 40 Hz according to almost all studies examining 40‐Hz ASSR, ASSR at 40 Hz was measured.…”
Section: Studies Of Auditory Steady‐state Responsementioning
confidence: 99%
“…Other mental conditions such as bipolar disorder or affective psychosis show similar ASSR deficits, indicating that ASSR may provide a useful index for distinguishing these conditions from major depressive disorder ( 12 , 16 ). However, the utility of ASSR as a biomarker remains limited by the small sample size (<100) in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…40 Hz amplitude-modulated stimuli (e.g., amplitude-modulated tones, white noise, or click trains) can be used to entrain the ASSR, which peaks around 40 Hz in humans (Azzena et al, 1995; Hari et al, 1989) and can be measured using electroencephalography (EEG) or magnetoencephalography (MEG). ASSR abnormalities have been observed in autism spectrum disorders (Wilson et al, 2007), schizophrenia (Brenner et al 2003; Hayrynen et al, 2016; Kwon et al, 1999; Light et al, 2006; O’Donnell et al, 2013; Roach et al, 2013; Spencer et al, 2008; Thune et al, 2016), and bipolar disorder (Isomura et al, 2016; Maharajh et al, 2007; O’Donnell et al, 2004; Oda et al, 2012; Rass et al, 2010). Heritability of these abnormalities has been suggested, as they have also been identified in first-degree relatives of individuals with autism (Rojas et al, 2011) and schizophrenia (Hong et al, 2004; Rass et al, 2012).…”
Section: Introductionmentioning
confidence: 99%